Karl-Johan Hemmersam, Jørgen Husballe, Erik Bach Nielsen, Jørgen Olsen, Verden i konflikt. International politik 1945-1987, København: Munksgaard, 1988, 288 s., kr. 178,00. - Larsen, Arne (Politica, 1988)
-